ANALISIS PROGRAM PENDIDIKAN KECAKAPAN WIRAUSAHA PELATIHAN TATA KECANTIKAN KULIT DI SANGGAR KEGIATAN BELAJAR (SKB) KOTA PEKANBARU - Anita Anita; Wilson Wilson; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: The purpose of this study is to describe the results of the analysis of entrepreneurial skills training programs on skin beauty training in the Learning Learning Studio (SKB) of Pekanbaru City, which covers the objectives of the program, students, educators, curriculum, facilities for learning and evaluation. This study used a descriptive method with a qualitative approach aimed at knowing the analysis of educational training programs for entrepreneurial skills on skin training. This study consisted of one variable, namely the educational skills education program with 6 indicators, 18 sub-indicators. The subjects of this study were 7 people consisting of 2 key informants, 4 control persons and 1 observer-informant. Techniques used for data collection were observation, interviews and documentation. The data analysis technique uses data reduction, display data and data verification. The results of this study indicate that the entrepreneurship skills training program organized by the Pekanbaru City Learning Activity Center (SKB) with 6 indicators and 18 sub-indicators there are 3 sub-indicators that are not in compliance with the technical guidelines of the Ministry of Education and Culture, namely 1) sub-indicator time mentor indicators, 3) sub-indicators practice room. In the sub-indicator of the implementation of theoretical and practical training, only 80 hours of lessons can be taken from 150 hours. In the mentoring sub-indicator, only one month is performed from the three-month period. While in the exercise room sub-indicator, the available space does not match the size of the number of students participating in the training, so that learning is not satisfactory. To overcome this incompatibility, managers and members of entrepreneurial skills training programs are expected to have a sense of responsibility in the performance of their duties, so that the program organized by the Pekanbaru City Learning Center for Students (SKB) is implemented and results in accordance with the technical guidelines for educational programs for entrepreneurial skills. The head of the Pekanbaru City Learning Activity Center (SKB) is then hoped that the learning facilities will be equipped to create favorable and comfortable learning conditions.Key Words: Analysis, Program Entrepreneurial Skills Education, Training in Skin Beauty